2019
DOI: 10.1016/j.ijoa.2018.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Serious adverse events attributed to remifentanil patient-controlled analgesia during labour in The Netherlands

Abstract: Background: During labour, remifentanil patient-controlled analgesia is used as an alternative to neuraxial analgesia. Remifentanil is associated with hypoventilation and respiratory depression but the frequency of serious maternal and neonatal adverse events is unknown. The aim of this study was to estimate the number of serious adverse events attributed to the use of remifentanil patient-controlled analgesia during labour in The Netherlands and to investigate the circumstances (e.g. monitoring, practice devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…It can be used as an effective replacement for patient-controlled epidural analgesia in parturients with contraindications of spinal block, refusal of epidural puncture or unsatisfactory coordination of anesthesia position, especially for those with rapid progress of labor [26]. During the implementation of this method of labor analgesia, one gives maternal oxygen, provide perfect and continuous maternal and fetal monitoring measures [27], implement doula one-to-one delivery support [28], provide 24 h full-time anesthesiologists in the delivery room [29], and prepare for neonatal asphyxia resuscitation to the greatest extent to ensure the safety of the mothers and the newborn infants [30].…”
Section: Discussionmentioning
confidence: 99%
“…It can be used as an effective replacement for patient-controlled epidural analgesia in parturients with contraindications of spinal block, refusal of epidural puncture or unsatisfactory coordination of anesthesia position, especially for those with rapid progress of labor [26]. During the implementation of this method of labor analgesia, one gives maternal oxygen, provide perfect and continuous maternal and fetal monitoring measures [27], implement doula one-to-one delivery support [28], provide 24 h full-time anesthesiologists in the delivery room [29], and prepare for neonatal asphyxia resuscitation to the greatest extent to ensure the safety of the mothers and the newborn infants [30].…”
Section: Discussionmentioning
confidence: 99%
“…Significantly higher concentrations compared to our pilot study can be expected also in other remifentanil PCA protocols as demonstrated in the study by Shen et al (8) since in some practices, and possible future efficacy/safety studies, the administration of remifentanil is used or expected to last through the whole delivery, particularly throughout the expulsion phase, where effective pain control is also most needed and desired, resulting in much higher blood concentrations of remifentanil at the time of delivery. This applies to neonatal and maternal samples whose concentrations are expected to be approximately two-fold higher than that of the neonates, and hence, the mothers might be at higher risk of serious adverse events (1,18,33), underlining the need for appropriate dose-finding studies combined with individualization based on clinical assessment. Other venous and capillary blood sampling methods could also be used in conjunction with our analytical methods, such as volumetric absorptive microsampling (VAMS) (34), finger-prick (35), and heel-prick sampling (36).…”
Section: Dbs-specific Validation Parametersmentioning
confidence: 99%
“…Even though the parturient heart and ventilatory function or saturation must be constantly monitored by an anaesthesiologist, some cases of respiratory arrest in mothers have been associated with remifentanil use during labour (14)(15)(16)(17)(18). Moreover, the short-and long-term effects on infants caused by remifentanil use during labour have not been fully characterised either (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, all women could consult with an anesthesiologist regarding her optimal analgesia options prior to labor, enabling selection of the most appropriate options, based on individualized information [ 4 ••]. A more diverse, older laboring population may have associated concurrent comorbidities such as cardiovascular conditions, thromboembolism, and cardiomyopathy which are more common causes of peripartum death [ 5 ].…”
Section: Pre-admission Obstetric Anesthesiologist Consultationmentioning
confidence: 99%